Efeito da matéria-prima na reologia e viscosidade da pasta de detergente - Nogueira, Caroline Alves (Universidade Federal de São Carlos, 2020)
The present work aims to study the rheology, viscosity and cost of powder detergent when changing a raw material. The construction of the rheological profile has the purpose of verifying the compatibility of the new formula to the equipment already existing in the plant, as there is no interest in spending on the acquisition of pumps and other important items for the displacement of the detergent mixture to a drying tower. In the case of viscosity, there is the possibility of reducing water in the gas-saving formula, because if the new raw material allows this reduction in viscosity, the reduction of water becomes viable. A cost analysis will be carried out to verify whether the exchange will be financially feasible. For viscosity measurements, a rotary viscometer is used, keeping the temperature constant, as well as the speed of rotation. A reduction in viscosity was found to have decreased only for a raw material 1, and not expressed for a raw material 2, which was considered inadequate to continue in the project, in addition, it was also observed that this benefit observed for a raw material 1 existed for a water reduction in the formula of up to 7%. After this verification, the current sample containing standard water level as well as the sample containing raw material 1, however, containing water level 7% below the standard, were subjected to analysis on a capillary rheometer, where a curve was generated for each sample. It was found that both are similar as rheology and viscosity, therefore, a raw material 1 was considered adequate to replace the current raw material. The formula cost, on the other hand, was calculated from the prices, purity and percentage of dosage of the ingredients, and the cost of complete drying gas was based on the existing process data for the standard humidity. Using this proportion, the estimated gas value for the new humidity was reached. From calculations calculations, it was estimated a savings of approximately 10% in relation to the current values of formula and drying gas. Therefore, the raw material exchange project will proceed to the implementation phases.
Effect of the raw material on the rheology and viscosity of the detergent paste
Keywords: Reologia; Viscosidade; Economia de gás; Perfil reológico; Análise de custo; Rheology; Viscosity; Gas savings; Rheological profile; Cost analysis; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA